Determinants of the Performance of Provincial Governments in Indonesia - Hakim, Luqman; Nurhenti, Enda (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2020)
The study was conducted to determine the determinants of provincial government performance in Indonesia. Research with a quantitative approach. The sampling method was purposive sampling with a research sample of 33. They are collecting data with the 2016 fiscal year financial reports at BPK RI. The research was conducted with descriptive statistical analysis and using multiple linear regression analysis. The results of this study indicate that the characteristics of the Regional Government and LHP BPK RI simultaneously / jointly affect the performance of Provincial Governments in Indonesia, but partially it is concluded that the variables of regional size, level of regional wealth, population, and BPK audit opinion have no significant effect on performance. Provincial Governments in Indonesia. Meanwhile, the BPK audit findings variable has a significant negative effect on provincial governments performance in Indonesia.